Safety and Efficacy of Atezolizumab in Understudied Populations with Pretreated Urinary Tract Carcinoma: Subgroup Analyses of the SAUL Study in Real-World Practice. Issue 2 (9th August 2021) - Merseburger, Axel S.; Castellano, Daniel; Powles, Thomas; Loriot, Yohann; Retz, Margitta; Voortman, Jens; Huddart, Robert A.; Gedye, Craig; Van Der Heijden, Michiel S.; Gurney, Howard; Ong, Michael; de Ducla, Sabine; et al.
Abstract : Purpose: Atezolizumab is an established treatment option for pretreated urothelial carcinoma, demonstrating efficacy in phase II/III trials. The SAUL study enrolled a broader patient population to determine safety and efficacy in underrepresented subgroups. Materials and Methods: Patients with metastatic urinary tract carcinoma received atezolizumab 1, 200 mg every 3 weeks until disease progression, unacceptable toxicity, loss of clinical benefit, or patient/physician decision. The primary endpoint was safety. Efficacy was a secondary endpoint. Analyses by programmed cell death ligand-1 (PD-L1) status, age, Eastern Cooperative Oncology Group performance status (ECOG PS) and renal impairment were prespecified; post hoc analyses explored outcomes by tumor location. Results: A total of 1, 004 patients were enrolled. Subgroup analyses in patients with older age, renal impairment, or upper tract urothelial carcinoma showed safety and efficacy similar to those in patients without these characteristics. Patients with ECOG PS 2 had clinical features typically associated with aggressive disease; median overall survival was 2.3 months versus 10.0 months in patients with ECOG PS0/1. Patients with PD-L1 expression on ≥5% of tumor-infiltrating immune cells tended to have better outcomes than those with <5% PD-L1 expression, although conclusions on the relative efficacy of atezolizumab cannot be drawn from this single-arm study. Conclusions: The understudied populations included in the SAUL study had similar outcomes to those in more selected populations included in phase II/III trials of atezolizumab, except for those with ECOG PS 2. Age ≥80 years and/or creatinine clearance <30 ml/minute does not preclude administration of atezolizumab; however, treatment risk versus benefit must be carefully assessed in patients with ECOG PS 2.